Brother Slattery Wins an Essay Contest: An Irish Christian Brother’s Influence on Education Reform in 1890s Newfoundland - Ralph, Rebecca Faye (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2021)
In 1890, the Newfoundland government held an essay contest to solicit opinions on how best to reform its education system. There was widespread acknowledgment that the system was failing to provide a quality education for the colony’s children. The threat to churches’ control over schools led Irish Catholic Christian Brother John Slattery to enter the essay contest. Slattery was victorious, though his win was dubious. He proposed a church-led conservative approach to educational reform, which led to the rise of a cooperative denominational paradigm that entrenched church control over schooling in Newfoundland and Labrador for more a century.